Comparison of the therapeutic effects and side effects of tadalafil and sildenafil after surgery in young infants with pulmonary arterial hypertension due to systemic-to-pulmonary shunts. (29th May 2017) - Sabri, Mohammad Reza; Bigdelian, Hamid; Hosseinzadeh, Mohsen; Ahmadi, Alireza; Ghaderian, Mehdi; Shoja, Mohammad
Abstract: Young children with CHD and large systemic-to-pulmonary shunts eventually develop pulmonary hypertension. At present, phosphodiesterase type-5 inhibitors such as sildenafil have been used to control pulmonary pressure before and after cardiac surgery. Recently, tadalafil has been utilised in older children with similar efficacy, but it has been used to a lesser extent in young infants. From April, 2015 to June, 2016, 42 patients aged 3–24 months with a large septal defect and pulmonary arterial hypertension were randomly divided into two equal groups: one group received oral sildenafil (1–3 mg/kg/day every 8 hours), whereas the other group received oral tadalafil (1 mg/kg once a day) from 7–10 days before surgery to 3–4 weeks after surgery. During the first 48 hours after surgery, pulmonary artery-to-aortic pressure ratio and recorded systolic pulmonary artery pressures were not significantly different between the two groups (p>0.05); moreover, there were no differences in paediatric ICU length of stay, mechanical ventilation time, clinical findings of low cardiac output state, and echocardiographic data between the two groups (p>0.05). Most of the patients had no side effects, and only five patients had a minor with no significant difference in both groups (p=0.371). Tadalafil can be considered as an effective oral therapy for preoperative and postoperative pulmonary hypertension in young infants. It can be administered at a once-daily dose with an appropriate efficacy and safety profile as sildenafil, and therefore it can be considered as an alternative to sildenafil in young children.